2017
DOI: 10.18483/ijsci.1265
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of Glutathione-S-Transferase Gene (GSTP1) in Type 2 Diabetes Mellitus Patients in Basra Province/Iraq

Abstract: Glutathione S-transferases (GSTs) are enzymes that included, in a wide range of detoxifying reactions by conjugation of glutathione, to electrophilic material. Polymorphisms in the genes that are responsible for GSTs affect, the function of the GSTs. GSTs play an active role in protection of cell against oxidative stress mechanism. Polymorphisms of GSTP1 at codon 105 amino acids forms GSTP1 important site for bind of hydrophobic electrophiles and the substitution of Ile/Val affect substrate specially catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The characteristics of each study were summarized in Table 1 (Tab. 1) (References in Table 1: Yalin et al, 2007[ 35 ]; Oniki et al, 2008[ 20 ]; Bid et al, 2010[ 6 ]; Tsai et al, 2011[ 33 ]; Ramprasath et al, 2011[ 21 ]; Amer et al, 2011[ 4 ]; Moasser et al, 2012[ 19 ]; Gönül et al, 2012[ 10 ]; Grubisa et al, 2013[ 11 ]; Mastana et al, 2013[ 17 ]; Vats et al, 2013[ 34 ]; Rao et al, 2014[ 22 ]; Abbasi et al, 2014[ 1 ]; Zaki et al, 2015[ 36 ]; Stoian et al, 2015[ 29 ]; Mergani et al, 2016[ 18 ]; Rasheed et al, 2016[ 23 ]; Ahmed and Al-Bachary, 2017[ 2 ]). The studies included in the present meta-analysis were conducted on different ethnic populations: 14 studies included a Caucasian population, 2 studies included an Asian population, and 2 studies included an African population.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics of each study were summarized in Table 1 (Tab. 1) (References in Table 1: Yalin et al, 2007[ 35 ]; Oniki et al, 2008[ 20 ]; Bid et al, 2010[ 6 ]; Tsai et al, 2011[ 33 ]; Ramprasath et al, 2011[ 21 ]; Amer et al, 2011[ 4 ]; Moasser et al, 2012[ 19 ]; Gönül et al, 2012[ 10 ]; Grubisa et al, 2013[ 11 ]; Mastana et al, 2013[ 17 ]; Vats et al, 2013[ 34 ]; Rao et al, 2014[ 22 ]; Abbasi et al, 2014[ 1 ]; Zaki et al, 2015[ 36 ]; Stoian et al, 2015[ 29 ]; Mergani et al, 2016[ 18 ]; Rasheed et al, 2016[ 23 ]; Ahmed and Al-Bachary, 2017[ 2 ]). The studies included in the present meta-analysis were conducted on different ethnic populations: 14 studies included a Caucasian population, 2 studies included an Asian population, and 2 studies included an African population.…”
Section: Resultsmentioning
confidence: 99%
“…In overall there was no significant association between the study polymorphism and the risk of T2DM under codominant (Figure 1 (Fig. 1) ; References in Figure 1: Yalin et al, 2007[ 35 ]; Oniki et al, 2008[ 20 ]; Bid et al, 2010[ 6 ]; Tsai et al, 2011[ 33 ]; Ramprasath et al, 2011[ 21 ]; Amer et al, 2011[ 4 ]; Moasser et al, 2012[ 19 ]; Gönül et al, 2012[ 10 ]; Grubisa et al, 2013[ 11 ]; Mastana et al, 2013[ 17 ]; Vats et al, 2013[ 34 ]; Rao et al, 2014[ 22 ]; Abbasi et al, 2014[ 1 ]; Zaki et al, 2015[ 36 ]; Stoian et al, 2015[ 29 ]; Mergani et al, 2016[ 18 ]; Rasheed et al, 2016[ 23 ]; Ahmed and Al-Bachary, 2017[ 2 ]), dominant (Figure 2A (Fig. 2) ; References in Figure 2: Yalin et al, 2007[ 35 ]; Oniki et al, 2008[ 20 ]; Bid et al, 2010[ 6 ]; Tsai et al, 2011[ 33 ]; Ramprasath et al, 2011[ 21 ]; Amer et al, 2011[ 4 ]; Moasser et al, 2012[ 19 ]; Gönül et al, 2012[ 10 ]; Grubisa et al, 2013[ 11 ]; Mastana et al, 2013[ 17 ]; Vats et al, 2013[ 34 ]; Rao et al, 2014[ 22 ]; Abbasi et al, 2014[ 1 ]; Zaki et al, 2015[ 36 ]; Stoian et al, 2015[ 29 ]; Mergani et al, 2016[ 18 ]; Rasheed et al, 2016[ 23 ]; Ahmed and Al-Bachary, 2017[ 2 ]) and allele genetic models (Figure 2B (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies regarding the association between GSTP1 polymorphism and the risk of T2DM yielded controversial results [23,24,25,28,29,34,42,45,46,47]. Some studies suggested that the GSTP1…”
Section: Discussionmentioning
confidence: 99%